Phenotyping Determination of in vivo CYP2D6 Enzyme Activity Used as A Probe Debrisoquine in Swiss Black, Holstein, Simmental and Eastern Anatolian Red Cow Breeds - Sakin, Fatih; Baydar, Ersoy; Servi, Kadir; Atessahin, Ahmet; Dagoglu, Gurdal (Kafkas Univ, Veteriner Fakultesi Dergisi, 2013)
In the current study was carried out to determine phenotyping of in vivo CYP2D6 enzyme activity used as a probe debrisoquine (DEB) in Swiss Black (SB), Holstein (HOL), Simmental (SI) and Eastern Anatolian Red (EAR) cows. In the study, totally 60 cows, fifteen cows from each breed, were used. DEB was application at 0.5 mg/kg. Urine samples were collected throughout 12. and 24th h after DEB application. The metabolic (DMR) and recovery (DRR) rates of DEB in urine samples were calculated to evaluate the in vivo activity of CYP2D6 enzyme activity. The DMR value of EAR at 12th h were significantly higher than those others (P<0.01) while this value significantly lower in EAR compared to that of others (P<0.01). The phenotyping CYP2D6 enzyme activity of EAR at 12th h was considered as poor metaboliser (PM) while this phenotype was extensive metabolizer (EM) in SB, HOL and SI cows. In conclusion, it can be considered that urine samples taken at 12th h after DEB administration at dose of 0.5 mg/kg as probe can be used to determine in vivo phenotyping of CYP2D6 enzyme activity in cows. Besides, in implementation of treatment with drugs that are substrates of CYP2D6 in cows, it can be concluded that these drugs will be metabolized more slowly, and the duration time of body and effect durations of action will be increased in EAR cows.
İsviçre esmeri, Holştayn, Simental ve Do?u Anadolu Kırmızısı irkı i?neklerde prob i?laç olarak debrizokin kullanılarak in vivo cyp2d6 enzim aktivitesinin fenotipik belirlenmesi
Keywords: CYP2D6; Cows; Debrisoquine; Phenotyping